2022
DOI: 10.1002/adom.202102727
|View full text |Cite|
|
Sign up to set email alerts
|

Highly Luminescent and Multifunctional Zero‐Dimensional Cesium Lanthanide Chloride (Cs3LnCl6) Colloidal Nanocrystals

Abstract: all-inorganic ternary perovskite nanocrystals (NCs) are widely studied for their promising characteristics as semiconducting materials for optoelectronic applications owing to their high photoluminescence (PL) quantum yields (PLQYs) and narrow emission bandwidths. [3] The optical properties of perovskite NCs can be tuned by tailoring their sizes, compositions, and confined dimensions. [4][5][6][7] In addition to size confinement on the nanoscale, the dimensionality of ternary metal halides can be defined based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 92 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…Blue PL of 0D Cs 3 LnCl 6 (Ln: lanthanide) NCs under UV excitation have been previously reported by our group. 35 The 0D host emission from Cs 3 LnCl 6 NCs exhibit a broadband, asymmetric emission profile. In contrast, Cs 3 EuCl 6 NCs exhibit highly symmetric and very narrow PL spectra, which is inconsistent with the PL characteristic of 0D Cs 3 LnCl 6 NCs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Blue PL of 0D Cs 3 LnCl 6 (Ln: lanthanide) NCs under UV excitation have been previously reported by our group. 35 The 0D host emission from Cs 3 LnCl 6 NCs exhibit a broadband, asymmetric emission profile. In contrast, Cs 3 EuCl 6 NCs exhibit highly symmetric and very narrow PL spectra, which is inconsistent with the PL characteristic of 0D Cs 3 LnCl 6 NCs.…”
Section: Resultsmentioning
confidence: 99%
“…Colloidal Cs 3 EuCl 6 and Cs 3 TbCl 6 NCs were synthesized by the previously reported heating-up method. 35,45 The reaction was performed at 260 °C for 1 h. The reaction solution was transparent yellow before heating and turned opaque brown with europium and opaque white with terbium during the reaction, indicating the formation of NCs. As-synthesized NCs exhibit high colloidal stability in nonpolar solvents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 A small percentage of lead-free perovskite NCs have been found to exhibit narrow-band blue light emission. 18–22 For example, Cs 3 Sb 2 Br 9 NCs obtained through ligand-assisted reprecipitation synthesis, display a narrow full width at half maximum (FWHM) (41 nm) in the blue region. 23 Han et al reported that Cs 3 Bi 2 Br 9 NCs exhibit blue emission at 468 nm with a FWHM of 40 nm.…”
Section: Introductionmentioning
confidence: 99%